Health Belief Model Predictors of Medication Adherence Among Patients With Hypertension: A Cross-Sectional Study - Rahmat Hidayat; Nur Ilah Padhila; Muhammad Hisyam (An Idea Health Journal, 2026)
Background: Hypertension is a global health problem. More than 1.28 billion adults worldwide suffer from hypertension, but only 21% have their blood pressure under control. This is because many patients do not consistently follow medication recommendations. The Health Belief Model (HBM) is a theoretical framework that can be used to understand health behaviors, including medication adherence. Therefore, it is necessary to analyze the relationship between HBM components and medication adherence levels in hypertensive patients. Methods: This study was a quantitative cross-sectional design. The sample consisted of hypertensive patients undergoing antihypertensive therapy in Makassar City. The sample criteria were hypertensive patients, undergoing antihypertensive medication, and aged 18 years and older. The instruments consisted of the HBM Questionnaire and the Morisky Medication Adherence Scale (MMAS-8). Results: Of the 85 respondents, 44 (51.8%) were female, compared to 41 (48.2%) males. The highest age group was 56 – 65 years old (37) (43.5%) and the lowest group was >65 years old (9) (10.6%). The religion was Islam (65) (76.5%), Christianity (17) (20%) and Buddhism (3.5%). The highest ethnic group was Makassar (35) (41.2%) and the lowest were Ambon, Minang, and Manado each (1) (1.2%). Marital status was married (77) (90.6%) and unmarried (8) (9.4%). The highest occupation was housewife (31) (36.5%) and the lowest was private employee (2) (2.4%). The HBM level was 99.85, CI 91.35-108.35, SD 39.413. The level of medication adherence was 6.35, CI 6.08-6.62, SD 1.248. HBM level in the Vulnerability domain 16.29, CI 14.39-18.20, SD 8.837. Severity Domain 9.40, CI 8.32-10.48, SD 4.993. Threat Domain 9.85, CI 8.73-10.96, SD 5.167. Benefit Domain 22.18, CI 19.71-24.65, SD 11.452. Barrier Domain 17.51, CI 15.86-19.15, SD 7.629. Self-Efficacy Domain 24.62, CI 23.86-25.39, SD 3.542. The correlation between HBM and Medication Compliance appears significant with a p value <0.001 with a moderate correlation value of r 0.527. The HBM components, namely the vulnerability domain, showed a moderate correlation of r 0.559, the severity domain a moderate correlation of r 0.553, the threat domain a moderate correlation of r 0.527, the benefits domain a moderate correlation of r 0.521, the barriers domain a moderate correlation of r 0.463, and the self-efficacy domain a weak correlation of r 0.326. Conclusion: A significant correlation appears between the HBM and medication adherence. Moderate correlations are found in the domains of perceived vulnerability, perceived severity, perceived threat, perceived benefits, and perceived barriers, while the self-efficacy domain appears weak.